Cadmium effect on optical properties of Cu2Zn1−xCdxSnS4 quinternary alloys nanostructures. (April 2015) - Ibraheam, A.S.; Al-Douri, Y.; Hashim, U.; Ghezzar, M.R.; Addou, A.; Ahmed, Waleed K.
Highlights: Exploring Cu2 Zn1 − x Cd x SnS4 nanostructures. Synthesis the optical properties of Cu2 Zn1 − x Cd x SnS4 nanostructures. Characterize the Cu2 Zn1 − x Cd x SnS4 nanostructures. Verify refractive index and optical dielectric constant. Elaborate the electrical characteristics of Cu2 Zn1 − x Cd x SnS4 nanostructures. Abstract: While efforts have been made to synthesize quaternary alloy nanostructures with high surface area for application in many fields, a detailed exploration of quinternary alloy nanostructures has not been reported until now. This work investigates the optimum crystallization parameters for reducing crystal defects in Cu2 Zn1 − x Cd x SnS4 quinternary alloy nanostructures. Alloy nanostructures with different Zn and Cd contents were grown by a sol–gel method. The analytical results confirmed a multi-phase polycrystallinity of the samples, and the variations in their energetic transitions and optical properties with Cd content were investigated. The morphology and topography of the samples were also observed. Our results are supported by several related studies in the literature.